Biocompatibility of Mineral Trioxide Aggregate Mixed with Different Accelerators: an Animal Study - Mitra Tabari; Maryam Seyed Majidi; Mahtab Hamzeh; Saeideh Ghoreishi (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Several additives have been introduced to decrease the setting time of MTA (mineral trioxide aggregate). For clinical applications, it is essential to investigate the biocompatibility of these materials. Purpose: The present study evaluated the tissue response to MTA that has been separately mixed with citric acid, calcium lactate gluconate (CLG), and Na2HPo4. Materials and Method: In this experimental study Twenty one Wistar rats were divided into three groups of 7, 14 and 30 days follow up periods. Sterile polyethylene tubes were subsequently filled with MTA separately mixed with distilled water, 0.1% citric acid, 0.43% calcium lactate gluconate (CLG) and 15% Na2HPO4 and afterwards implanted subcutaneously. Empty tubes were implanted as negative control. At the end of their respective periods, the animals were sacrificed by anesthetic overdose and a biopsy was performed. The inflammatory responses were scored, classified and statistically analyzed using Kruskal-Wallis and Man-Whitney tests. Statistical significance was defined as p< 0.05. Results: There was no significant difference between test groups in any time period after implantation but the mean values of inflammatory responses were significantly more than that of the negative control group (p> 0.05). The mean values of inflammatory responses were decreasing over time in all test groups. These values did not significantly differ in any group except the CLG and Na2HPO4 groups. Conclusion: The inflammatory responses induced by MTA mixed with citric acid and MTA mixed with Na2HPo4 were comparable to that of the control MTA. MTA mixed with CLG provoked a moderate-to-severe inflammatory response at 7 days after implantation, so further study is required before clinical application of this cement.